Oppression Toward The Marginal Society In Patricia Mccormickâ€™s Novel â€œSoldâ€ - Neisya; Merry Julia Pardede (Journal of English Teaching, Linguistics and Literature, 2020)
The major intention of this research is to analyze the causes of oppression toward the marginal society and the main character’s resistance to the oppression in Patricia McCormick’s novel Sold. The data was analyzed by using Spivak’s subaltern theory. The objectives of the research were to find out the causes of oppression and the main character’s resistance toward it. The study designed is a descriptive qualitative method. The study results showed that the oppression was caused by four factors: (1) patriarchy (2) rural poverty (3) capitalism (4) age. Meanwhile, the main character’s resistance toward the oppression was (1) an act of obedience (2) enduring the suffering of fear (3) feeling dying, worthless, disgusted with herself (4) expecting freedom (5) seeking comfort by pretending (6) expecting the law of stopping the human trafficking (7) learning English and Hindi language secretly (8) longing for affection.